Pristimerin inhibits neuronal inflammation and protects cognitive function in mice with sepsis-induced brain injuries by regulating PI3K/Akt signalling - Weimin Xue; Yaqiang Li; Mei Zhang (Taylor & Francis Group, 2021)
Context Sepsis is a systemic inflammatory disease; pristimerin exhibits strong antibacterial, anti-inflammatory and antioxidant properties. Objectives We explored whether pristimerin protected against cognitive dysfunction and neuroinflammation in C57BL/6 J mice with sepsis-induced brain injuries. Materials and methods Sepsis was induced by intraperitoneal administration of 2 mg/kg lipopolysaccharide (LPS). C57BL/6 J mice were separated into four groups (n = 10 per group): positive control, negative control, pristimerin 10 mg/kg and pristimerin 100 mg/kg. Pristimerin was administered orally for 28 days prior to LPS administration and for six days thereafter. Behavioural changes were assessed one day after LPS administration using the Morris water maze and via neurological dysfunction scoring. Molecular pathogenesis was explored by measurement of malondialdehyde, superoxide dismutase, reactive oxygen species and inflammatory cytokine levels in mouse brains. Neuronal apoptosis was evaluated using the TUNEL assay. The levels of p-Akt/Akt, p-PI3K/PI3K, mTOR, Bax, Bcl-2 and caspase-3 proteins were determined via Western blotting. Results Pristimerin improved cognitive function and reduces the neurological score to 1.15 ± 0.03. Pristimerin significantly reduced all cytokine levels: TNF-α by 18 ± 0.6 pg/mg, IL-1β by 43 ± 1.3 pg/mg and IL-6 by 34 ± 1.12 pg/mg. There was significant (p < 0.01) improvement in PI3K/Akt signalling and histopathological changes in the brain tissue of sepsis induced brain injured rats. Conclusions Pristimerin ameliorated neuronal injury by regulating PI3K/Akt signalling in mice with sepsis-induced brain injuries. Pristimerin may merit further development for clinical applications.